Tajdidun Nikah Sebagai Upaya Penguatan Keluarga Sakinah (Studi Kasus di Desa Rejoagung Kecamatan Ngoro Kabupaten Jombang) - Ummu Rofi’ah; Wakid Evendi (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
In the customary practices of the Javanese Muslim society, there are often certain approaches employed to prevent divorces. This approach is commonly referred to as "tajdidun nikah," which translates to the renewal of marriage. This strategy is typically employed when a household faces numerous challenges or prolonged conflicts, leading to a decline in the harmony between spouses. This research aims to recognize and examine the occurrence of the tajdidun nikah phenomenon within the Rejoagung village community in Ngoro Jombang, in accordance with Islamic law. Through a descriptive qualitative methodology, the study collected data through participatory observations, in-depth interviews, document analysis, and applied an analysis framework based on the model developed by Miles and Huberman. The findings of the study concluded that the practice of tajdidun marriage in Rejoagung village, Ngoro District, Kabupaten Jombang, is a heritage that has been transmitted through generations. It represents an effort by married couples to reinforce their strained marital relationships, which could potentially lead to divorce. From an Islamic legal perspective, this practice is deemed permissible, as it offers numerous advantages, as long as the process adheres to Sharia principles. Couples who have embraced this tradition tend to experience greater harmony, tranquility, and enduring relationships within their households.